Relationship between the jaw-closing force and dietary form in older adults without occlusal support requiring nursing care - Rieko Moritoyo; Kazuharu Nakagawa; Kanako Yoshimi; Kohei Yamaguchi; Miki Ishii; Ryosuke Yanagida; Chizuru Namiki; Haruka Tohara (Scientific Reports, 2023)
Abstract In clinical practice, we encounter cases wherein older adults lacking occlusal support consume foods requiring mastication and adequate swallowing function. This study investigated the relationship between jaw-closing force (JCF) and dietary form in older adults without occlusal support requiring nursing care. This prospective cross-sectional study included 123 older adults requiring nursing care who lost their molar occlusal support and consumed food orally without dentures. JCF was defined as the force required for crushing food with the edentulous ridges or with the tooth and edentulous ridge while closing the mouth. Participants were classified into four groups based on the International Dysphagia Diet Standardization Initiative framework for recommended dietary forms. Basic information was collected, and tongue pressure and JCF were measured. Differences in JCF were analyzed using one-way analysis of variance, while factors related to dietary form were evaluated using ordinal logistic regression analysis. Significant differences in JCF were observed among the four groups. Factors such as the Barthel Index, tongue pressure, and JCF were dietary form-related. Our findings suggest that older adults requiring nursing care tend to have higher JCF when consuming meals requiring mastication. Therefore, JCF could serve as an index for determining appropriate dietary forms in this population.